Is it feasible to use a humanoid robot to promote hand hygiene adherence in a hospital setting? - H. Worlikar; V. Vyas Vadhiraj; Aoife Murray; J. O'Connell; C. Connolly; J.C. Walsh; D.T. O'Keeffe (Elsevier, 2022)
Summary: Healthcare associated infections (HCAI) are a prevalent preventable cause of morbidity and mortality. Improving hand hygiene adherence is important for HCAI prevention. In this feasibility study, the objective was to determine if a humanoid robot could act as a novel single reminder intervention to improve hand hygiene adherence in a hospital setting. DAVE, a social humanoid robot, improved hand hygiene adherence at the entrance to a tertiary hospital and outpatient department, which was low at baseline, by 29%. DAVE shows promise as a novel intervention to improve hand hygiene adherence.